Seroprevalence of Leptospira in animals: potential reservoirs for humans in Peru – a scoping review - Santana, Cirene (2025)
Leptospirosis is a zoonotic disease of worldwide distribution and great public health importance, with animals as the main reservoirs for humans. The objective was to conduct a systematic search of all available information on pathogenic serogroups of Leptospira spp. in different animal species in Peru, during the period 2003 to 2023. Six databases were included: «PubMed», «SciELO», «Cybertesis», «RENATI», «Google Scholar» and «Web of Science». Thirty-five studies were obtained, including theses and scientific publications, mainly conducted in Lima (24.39%, n=10) and Piura (12.2%, n=5). The studies most frequently included dogs (34.28%, n=12), wild animals (28.57%, n=10), and South American camelids (17.14%, n=6). The main serogroups identified were Icterohaemorrhagiae, Canicola, Pomona, and Iquitos. Despite the diversity found, no uniform cutoff point for determining seropositivity was found, ranging from 1:50 to 1:400. The findings demonstrate a low frequency of studies in regions outside of Lima, which is more frequent in dogs compared to other animal species.